Demonstrating Affection, Empathy and Playful Engagement as Factors Influencing Parental Discipline Strategies - John Mark Asio (People and Behavior Analysis, 2023)
Parenting is both a skill to learn and master since it will give the offspring perspectives in life. To attain this unique ability, one must master the art of affection, engagement and discipline towards the child. This study analyses affection, empathy, and play engagement as predictors of discipline strategies for parents of a primary school in the Philippines. The study used a descriptive-correlation research design with the survey as the primary gathering tool. One hundred forty-four parents voluntarily participated in the survey, which commenced in March and ended in April 2023. To analyze the data, the proponent used descriptive and inferential statistics. The study found that parents always show their affection and empathy, try to engage in play and establish discipline strategies. In addition, the computation also found a moderate relationship between showing affection and empathy and engaging in play with the establishment of discipline strategies among parents. Regression analysis also confirmed that showing affection and empathy and engaging in play are predictors of establishing discipline strategies among parents.